2001
DOI: 10.1002/cne.1407
|View full text |Cite
|
Sign up to set email alerts
|

Architectonic identification of the core region in auditory cortex of macaques, chimpanzees, and humans

Abstract: The goal of the present study was to determine whether the architectonic criteria used to identify the core region in macaque monkeys (Macaca mulatta, M. nemestrina) could be used to identify a homologous region in chimpanzees (Pan troglodytes) and humans (Homo sapiens). Current models of auditory cortical organization in primates describe a centrally located core region containing two or three subdivisions including the primary auditory area (AI), a surrounding belt of cortex with perhaps seven divisions, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
414
4
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 458 publications
(458 citation statements)
references
References 117 publications
(207 reference statements)
37
414
4
3
Order By: Relevance
“…As shown in Table 2, the clusters of activity in the auditory region were bilaterally distributed, with the strongest activity in superior temporal gyrus/sulcus and middle temporal gyrus. These regions comprise auditory association areas along the presumptive belt and parabelt regions, which are thought to receive input directly from the primary auditory cortex in normal hearing primates and humans (Hackett et al 2001). In our study, we never observed greater activity in auditory cortex in control subjects than in implant users, regardless of the nature of the stimulus.…”
Section: Discussioncontrasting
confidence: 48%
“…As shown in Table 2, the clusters of activity in the auditory region were bilaterally distributed, with the strongest activity in superior temporal gyrus/sulcus and middle temporal gyrus. These regions comprise auditory association areas along the presumptive belt and parabelt regions, which are thought to receive input directly from the primary auditory cortex in normal hearing primates and humans (Hackett et al 2001). In our study, we never observed greater activity in auditory cortex in control subjects than in implant users, regardless of the nature of the stimulus.…”
Section: Discussioncontrasting
confidence: 48%
“…The initial cortical analysis of speech occurs bilaterally in core and surrounding superior auditory areas (see Hackett et al (2001) for relevant human auditory cortex anatomy). Subsequent computations (typically involving lexical-level processing) are largely left lateralized (with the exception of the analysis of pitch change; the analysis of voice; and the analysis of syllable-length signals), encompassing the STG, anterior and posterior aspects of the STS as well as inferior frontal, temporo-parietal and inferior temporal structures (see Poeppel et al (2004) for arguments and imaging evidence that speech is bilaterally mediated).…”
Section: Functional Anatomic Backgroundmentioning
confidence: 99%
“…during neurosurgery; Howard et al 2000;Brugge et al 2003). Post-mortem histological material is scarce and of relatively poor quality (Hackett et al 2001;Wallace et al 2002), and in vivo tracer studies in humans are currently not possible. The rhesus macaque monkey (Macaca mulatta) provides an animal model for the organization of auditory cortex (Rauschecker et al 1997;Rauschecker 1998;Kaas et al 1999;Kaas & Hackett 2000), and this can be supplemented by the (relatively few) anatomical and neurophysiological studies that have been conducted in humans (Liegeois-Chauvel et al 1991;Rivier & Clarke 1997;Howard et al 2000;Hackett et al 2001;Morosan et al 2001;Rademacher et al 2001;Wallace et al 2002;see Hall et al (2003) and Scott & Johnsrude (2003), for reviews).…”
Section: A Brief Overview Of Auditory Anatomy (A)mentioning
confidence: 99%